Online Writing Assessment during the Covid-19 Pandemic: Challenges, Options and Scenarios - Handayani, Fitri; Syarif, Hermawati (Proceeding of International Conference on Language Pedagogy (ICOLP), 2021)
Assessment is at the core of the teaching process. It shapes students’ understanding of the curriculum and determines their ability to progress. Choosing an assessment strategy is an important aspect of the curriculum planning process. Hence, in the context of this shift from face-to face learning to full-time online learning, several challenges arose including how to develop online writing assessment to the students. In particular, online assessment of students’ writing has become an unprecedented new situation for many English lecturers. The transition from face-to-face assessment to online assessment has been a new experience for many English lecturers who have never applied it before nor have background knowledge of its mechanisms and methods. The issue has raised an important point for English teaching practitioners and course designers regarding the strategies and challenges of this mandatory mode of assessment. From this perspective, the purpose of this paper is to provide an overview of online writing assessments in the COVID-19 pandemic era, including challenges faced by lecturers in conducting online assessments, as well as a set of recommendations for designing online assessment mechanisms and strategies that will result in a fair assessment process for all.